ANALISIS SISTEM AEROPONIK TERTUTUP PADA BUDIDAYA TANAMAN KENTANG (Solanum Tuberosum L.) DI UNIT PELAKSANA TEKNIS (UPT) BENIH INDUK HORTIKULTURAL (BIH) KUTAGADUNG BERASTAGI. - Marpaung, Posman H P; Siburian, Fandri; Sinaga, Nelly (Universitas Quality, 2024)
Agriculture plays an important role in economic, social and environmental development in Indonesia. As the main sector, agriculture contributes to food security, creates jobs, provides industrial raw materials, and is a source of foreign exchange for the country through exports of agricultural products. Apart from that, agriculture also plays a role in managing natural resources and the environment through sustainable agricultural practices. Agricultural development in rural areas can also strengthen rural development and improve community welfare (Septiana, 2019). controlling the plant's growing environment, aeroponic systems can ensure optimal growth throughout the year, increasing productivity and food security.Potatoes have always been one of the crucial food commodities in Indonesia. In fact, demand continues to increase from year to year. However, production is still fluctuating due to the unstable quality of the seeds. For this reason, it is hoped that a solution can help increase the amount of potato production by examining new discoveries in potato seed cultivation propagation techniques. Aeroponic technology is here to provide a solution to increase the quality of potato seed production. Aeroponics is a technique for cultivating seeds without soil and plant nutrition is obtained from water or a solution that is sprayed in the form of mist. The procedures carried out in the aeroponic technique are preparation of aeroponic equipment and boxes, preparation of potato seeds, planting potato plants, and maintenance (Febriansyah, 2020).